POLITICAL AWARENESS, KNOWLEDGE, AND PARTICIPATION RELATIONSHIP USING STRUCTURAL EQUATION MODELING APPROACH - Aidinil Zetra; Kartini Aboo Talib @Khalid; Ferra Yanuar; Susi Marisa (JWP (Jurnal Wacana Politik), 2022)
Political participation is fundamental in consolidating democracy in which political participation influences the legitimacy of society towards the running of a government. In elections, political participation could be considered community control over a government. Therefore, modeling the factors of political participation becomes essential. This cross-sectional study investigates the relationship between political awareness, political knowledge, and political participation of individuals living in Padang, Indonesia, and participating in the general election of 2020. This study employs the structural equation modeling (SEM) approach to construct the proposed model. The stability of SEM’s algorithm is checked using a reliability test. The performance of SEM and its algorithm is identified using the Bootstrap technique. The statistical tests proved that the proposed model is acceptable. This study found that political awareness has a positive and direct effect on political knowledge while political knowledge positively impacts political participation. It means that political awareness does not directly influence political participation. The political knowledge mediates it. This study suggests that individuals have to improve their public knowledge in the election to improve political participation. Meanwhile, political knowledge could be increased by improving political awareness. Indicator variables for each latent variable are also investigated in this study.